The dynamic ambivalence of adolescence in Emmanuel Dongala’s Johnny chien méchant (2002) and Tierno Monénembo’s L’Aîné des orphelins (2000) - Kate Mackenzie (Francosphères, 2024)
In Johnny chien méchant (2002) by Emmanuel Dongala and L’Aîné des orphelins (2000) by Tierno Monénembo, the figure of the adolescent narrator-protagonist serves to depict personal and social crisis in (post-)conflict environments in Central Africa. This article explores how the authors portray the dynamic ambivalence of adolescence in interaction with a world in flux, both through the subjective accounts of their narrator-protagonists and through narrative form. Dongala uses the device of twin narratives – ostensibly of victim and perpetrator – to depict contrasting paths through violent conflict, and to show the turmoil of each adolescent protagonist from within and without. Monénembo’s teenage narrator gives a disjointed account, moving back and forth between recollections of innocent, stable, pre-pubescent childhood and brash, volatile adolescence, separated by the extreme rupture of the 1994 genocide against the Tutsi in Rwanda. The agency of the adolescent is manifest in a dynamic interaction of self-formation, resistance, and engagement with the world – an interaction intensified by the context of conflict and the ambiguous power of the peer group, violence, and the sexed body. The unreliable first-person narrative voice serves both to shape and to undermine adolescent identity and to deny the reader a stable point of view. In their unsettling and ambivalent conclusions, both novels challenge the linear conception of the child in formation progressing towards ‘fully formed’ adulthood. Rather, adolescence emerges as symbol and embodiment of creative/destructive flux, holding out the fragile possibility of renewal.